A Case Report on the Management of Residual Calculi After Cholecystectomy Through Ayurveda Therapeutic Approaches - Afiya M Shoukkath; Sreeni T V (International Journal of Ayurveda and Pharma Research, 2025)
Cholecystectomy, the surgical removal of the gallbladder, is a commonly performed procedure worldwide, primarily indicated for symptomatic cholelithiasis and cholecystitis. While the procedure effectively eliminates the gallbladder as a source of stones, it does not eliminate the risk of calculi entirely. Residual calculi can occur after cholecystectomy, although it is relatively rare. If these calculi are identified within two years postoperatively, they are typically classified as residual; if discovered later, they may be termed as recurrent. A 50-year-old female patient with a history of chronic cholecystitis who underwent laparoscopic cholecystectomy four and a half years prior had experienced abdominal pain, which progressively worsened with each passing day and was associated with fever and nausea. She consulted the outpatient department at the Government Ayurveda Medical College, Thiruvananthapuram. The USG abdomen scan revealed multiple internal calculi in a gallbladder-like structure (Gall bladder stump) as a surgical remnant. She was treated with internal medications. She continued the medicines for two years with follow-ups every month, and the stones are completely gone after the due course of treatment. This management approach reveals that Ayurveda can provide promising and effective remedies in the management of residual calculi after cholecystectomy.